The impact of AIM2 inflammasome-induced pyroptosis on acute gouty arthritis and asymptomatic hyperuricemia patients - Chu, Jiyan; Tian, Jing; Li, Ping; Fu, Diyu; Guo, Lin; Sun, Rui (Frontiers in Immunology, 2024)
Objective: This study aimed to evaluate the role of absent in melanoma 2 (AIM2) inflammasome-mediated pyroptosis in the pathogenesis of acute gouty arthritis (AGA) and asymptomatic hyperuricemia(AHU). Methods: A cohort of 30 AGA patients, 30 AHU individuals, and 30 healthy controls (HC) was assembled. Demographic and biochemical data, along with blood samples, were collected. Serum double-stranded DNA (dsDNA) levels were quantified using a fluorescent assay. Transcriptomic and proteomic analysis of AIM2, Caspase-1, GSDMD, IL-1β, and IL-18 in peripheral blood mononuclear cells was performed using qRT-PCR and Western blot. Enzyme-linked immunosorbent assay (ELISA) was employed to measure serum IL-1β and IL-18. Spearman correlation analysis was utilized to assess relationships between variables. Results: Both AGA and AHU groups demonstrated elevated metabolic indicators and serum levels of dsDNA, IL-1β, and IL-18 compared to the HC group.AGA patients exhibited higher inflammatory markers than the AHU group. In the AGA group, there was a significant increase in the mRNA and protein levels of AIM2, Caspase-1, GSDMD, IL-1β, and IL-18 (P<0.05 to P<0.001). The AHU group showed higher AIM2, Caspase-1, GSDMD, and IL-18 mRNA levels than the HC group (P<0.001 to P<0.01), with a nonsignificant increase in AIM2, GSDMD, and IL-1β proteins (P>0.05). In contrast, Caspase-1 and IL-18 proteins were significantly higher in the AHU group (P<0.05). Notable correlations were observed between AIM2 protein expression and levels of Caspase-1 and GSDMD in both AGA and AHU groups. In the AGA group, AIM2 protein correlated with IL-1β, but not in the AHU group. The AIM2 protein in the AHU group was positively associated with IL-18, with no such correlation in the AGA group. Conclusion: AIM2 inflammasome may play a role in the inflammatory processes of AGA and AHU and that its activation may be related to the pyroptosis pathway.